GOALS OF MODERN EDUCATION IN THE PERSPECTIVE OF ISLAM - Mahdee Maduerawae; Muhammadridwan Lehnuh (Edusoshum : Journal of Islamic Education and Social Humanities, 2023)
Education is a cultural procedure to raise the degree and position of a human being that lasts a lifetime. Education will develop and always be directed at the transition period. Therefore, education must be designed in tandem with the rhythm of change and the development of the times. And to run with this, what are the goals of modern education today from an Islamic point of view? The purpose of this study is to analyze the objectives of modern education from the perspective of Islam in Indonesia. The method applied in this article is the library research or literature study method, in which the researcher examines relevant journals, notes, books, and literature and also reviews the results of available studies and other significant data. The results of the study show that the goals of modern education can answer the demands and needs for quality education. The quality of education can be measured by its contribution to solving problems that exist in society in a factual and real way so that the community can feel its impact.